Pengaruh Likuiditas, Profitabilitas, Leverage Terhadap Nilai Perusahaan, CSR Sebagai Pemoderasi - Natalia Tumanan; Dyah Ratnawati (STEKOM PRESS, 2021)
This research is meant to test the influence of liquidity, profitability, and leverage to the firm value with the corporate social responsibility as the moderating variable. Firm value describes the prosperity of the shareholders. Liquidity, profitability, leverage and corporate social responsibility are the factors which can be a consideration for investors in investing. Methods that used in this research is quantitative method using secondary data obtained through the company’s financial statements. The result of the research shows that: 1) Liquidity has an influence to the firm value. 2) Profitabilitry has an influence to the firm value. 3) Leverage has an influence to the firm value. 4) Corporate social responsibility is unable to moderate the influence of liquidity to the firm value. 5) Corporate social responsibility is unable to moderate the influence of profitability to the firm value. 6) Corporate social responsibility is unable to moderate the influence of leverage to the firm value.